Gardiner Spencer: capstone - Spencer, Gardiner, artist (Colorado State University. Libraries, 2025)
The artist's statement: Through coil building I am connected to very intuitive and ancient parts of the human experience. Since as long back as we have records for, people have satisfied the compulsion to mold clay into precious little objects with nothing but their hands. When I am doing the same, I feel as though I am doing what a human was meant to do, like a fish is meant to swim or a cat is meant to lay in a patch of sunlight. I am meant to make a cup. The blueprint of functionality that runs through my ceramic practice gives me something to chew on; I love the question of how much visual or sculptural interest you can fit into something that you need, like a butter dish or a cup. I transmute passion and personality into the clay through touch, and once these objects go into the world to serve their purpose, that love and intention seeps into the user's life. I am interested in seemingly simple shapes or motifs that hold a lot of joy. I gravitate towards flower shapes for the rims of vessels and softened undulating lines that highlight the clay's will. Whenever there is a moment in my work where something could be aesthetically endearing I don't deny myself of that opportunity. Visually, my work explores a sort of indulgence in simple pleasure, arguing that cuteness is something to be taken seriously.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery